University Teachers’ Perceptions of Screening Students’ Communication Skills: A Case Study from Speech Pathology - Johnson, Robyn; Purcell, Alison; Power, Emma; Thomson, Kate (International Journal of Practice-based Learning in Health and Social Care, 2019)
Excellent communication and interpersonal skills are necessary for allied health professionals to provide effective care/treatment and underpin the practice-based competencies allied health students must develop. Communication skills of first year speech pathology (SP) students are screened at the major Australian metropolitan university where this study took place. Final year students screen their first year peers as part of their practice-based education experience. Although this identifies first year students with communication difficulties, the perceived value to university teachers (academics and practice educators) has not been investigated. This study described university staff perceptions of screening the communication skills of first year SP students. The qualitative, descriptive design included two focus groups. The dataset was analysed thematically. The analysis revealed the staff perception of value in screening communication skills to inform student support. Two sub-themes contributing to this perception were ‘purpose of the screener’ and ‘content and administration of the screener’. Both staff groups strongly valued the screening process, stating that it is positive and useful. A similar screening process could identify first year students from a range of health fields with less skilled communication, who may require additional support to achieve competency.